The China Study quick & easy cookbook : cook once, eat all week with whole food, plant-based recipes - Sroufe, Del (BenBella Books, Inc., 2015)
"When it comes to meal planning, do you find yourself deciding between healthy foods and quick options? Do you stare at the contents of your fridge, wondering what you can easily throw together? Even on a busy schedule, your meals can be simple, healthy, and delicious! You shouldn't have to sacrifice health or taste for efficiency in the kitchen. Nobody knows this better than Chef Del Sroufe, author of the New York Times bestseller Forks Over Knives-The Cookbook and Better Than Vegan. In The China Study Quick & Easy Cookbook, Sroufe takes kitchen time management to the next level and provides busy home cooks with menu plans, pantry lists, and more than 100 delicious plant-based recipes that are quick, easy, and multipurpose. Edited by LeAnne Campbell, author of The China Study Cookbook, this book guides you to spend a couple of hours one day a week preparing meals ahead of time so that they come together with little effort throughout the week. And, best of all, every dish follows the nutrition standards set forth by The China Study, ensuring optimal healthful and quality eating with whole food recipes such as: Fruit and Vegetable Curry; Jerk Mushrooms; Quinoa Cakes; Banana-Coconut Macaroons The China Study and the China Study cookbooks have helped transform your health. Now, with a foreword by The China Study coauthor Thomas Campbell, The China Study Quick & Easy Cookbook is the next step in transforming your kitchen, your time, and your life"--